A importância do precedente do Superior Tribunal de Justiça no contexto estado democrático constitucional : uma análise crítica da chamada jurisprudência lotérica - Ribeiro, Julio Cesar Medeiros (2015)
This study investigates the historical origins of the legal traditions common law and civil law, in order to identify the peculiar traits of hybrid tradition that shapes the Brazilian legal system, pointing democratic deficiencies arising from the absence of a culture of judicial precedents and warning of the need to readjust the position of the Superior Court of Justice. With the focus directed to the Brazilian Federal-law, specifically in relation to the Superior Court of Justice, we sought to demonstrate that the transition from the state Legislature to the Constitutional State insertion of legal certainty as the foundation of the republic requires the reconstruction of the purpose of civil procedure as a means of rights protection, which both involve granting fair decisions, as the delivery of precedents to give unity, predictability and stability to the right. However in the context of the Constitutional Democratic State the duty unit corresponds to one of the speeches needed to give legitimacy to judicial action, the Superior Court of Justice continues to work as Superior Court, control judicial decisions "incorrect" and uniformity of jurisprudence, which causes the serious illness called lottery decision, consistent with the adoption of completely separate decisions to strictly similar cases.